Functional Disability of Children with Spina Bifida: Its Impact on Parents' Psychological Status and Family Functioning - Ulus, Y.; Tander, B.; Akyol, Y.; Ulus, A.; Tander, B.; Bilgici, A.; Kuru, O. (Informa Healthcare, 2012)
Objective: To evaluate the impact of functional disability of Turkish children with spina bifida (SB) on parents' psychological status and family functioning. Methods: Fifty-four children with SB and parents were included. The Functional Measure for Children (WeeFIM), Beck Depression Inventory (BDI), and Family Assessment Device (FAD) were used. Results: Mothers' BDI scores were significantly higher than fathers' (p<0.001). No significant effects of the knowledge of having children with SB before birth and the number of children in families on BDI scores and FAD sub-scores were found (p>0.05). According to multiple regression analysis; significant correlations with fathers' BDI were problem-solving (p0.012) and general functioning (p0.037) and with mothers' BDI was roles (p0.018). Only childrens age was found to be an influential variable on WeeFIM scores (p<0.001). Conclusion: Spina bifida healthcare should include psychological support to parents of these children and this support should be independent from disability level of children. © 2012 Informa UK Ltd. All rights reserved.
Keywords: Disability; Family Assessment Device; Family Functioning; Spina Bifida; WeeFIM